Symptom experiences in patients after heart transplantation. (May 2013) - Stiefel, Penelope; Malehsa, Doris; Bara, Christoph; Strueber, Martin; Haverich, Axel; Kugler, Christiane
Patients' perceptions of immunosuppression-related symptom experience impact on quality of life and medication adherence. Using The Modified Transplant Symptom Occurrence and Symptom Distress Scale capturing items on symptom occurrence and symptom distress, 261 heart transplant recipients reported on their symptom experiences. Symptoms occurring with the highest prevalence were tiredness, lack of energy, and nervousness. Men showed erectile dysfunction causing the most distress. Women and younger patients reported significantly higher levels of symptom distress. Distress levels increased with time after transplant. Investigating responses to immunosuppression-related symptom experiences should help develop interventional methods to support long-term outcome.